2013
DOI: 10.1186/2196-1042-14-49
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of shear bond strength of orthodontic brackets using trans-illumination technique with different curing profiles of LED light-curing unit in posterior teeth

Abstract: BackgroundAlthough using light-cured composites for bonding orthodontic brackets has become increasingly popular, curing light cannot penetrate the metallic bulk of brackets and polymerization of composites is limited to the edges. Limited access and poor direct sight may be a problem in the posterior teeth. Meanwhile, effectiveness of the trans-illumination technique is questionable due to increased bucco-lingual thickness of the posterior teeth. Light-emitting diode (LED) light-curing units cause less temper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
22
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 18 publications
(21 reference statements)
3
22
0
1
Order By: Relevance
“…However, scattering cannot be considered as an independent phenomenon since light propagation is composed of absorbed, transmitted and reflected light [14]. Our results are thus in line with the earlier conclusions that transillumination seems to be clinically viable curing method for bonding brackets to incisors but not to premolars [9,10]. The present in vitro study design does not allow analysis of the light scattering effects of the pulpal tissues that has been shown to exceed that of enamel and dentin [15].…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…However, scattering cannot be considered as an independent phenomenon since light propagation is composed of absorbed, transmitted and reflected light [14]. Our results are thus in line with the earlier conclusions that transillumination seems to be clinically viable curing method for bonding brackets to incisors but not to premolars [9,10]. The present in vitro study design does not allow analysis of the light scattering effects of the pulpal tissues that has been shown to exceed that of enamel and dentin [15].…”
Section: Discussionsupporting
confidence: 82%
“…As an alternative method to increase the degree of cure, light curing through the tooth has been suggested [7,8]. However, there are only a few studies that have investigated the viability of this curing method [9,10]. The results of Oesterle and Shellhart [9] showed that transillumination through extracted maxillary incisors resulted in sufficiently high bond strengths of brackets, particularly when the curing time was 50 s. From the clinical point of view, the optimal bond strength has been considered to be at least 5.9 MPa [11], whereas the risk for enamel fractures increases when the bond strength is higher than 9.7 MPa [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,2 Bracket rebonding requires additional appointments, delaying the treatment and potentially compromising the results. 3 Orthodontic brackets are often bonded using resin-based, light-cured composites due to greater control of working time relative to chemically cured composites.…”
Section: Introductionmentioning
confidence: 99%
“…34 Ayrıca LED ışık cihazlarının dişlerde ısı artışına neden olmadığı, diş çevresindeki yumuşak dokulara zarar vermediği, ergonomik olduğu ve transillüminasyonda (lingual yönden ışınlama) kullanılabildiği belirtilmektedir. 35,36 Oesterle ve ark. da yapmış oldukları araş-tırmada 100 adet insan üst santral kesici dişinde geleneksel tungsten-quartz halojen ışık kaynağı kullanarak transillüminasyon şeklindeki ışınlama-nın bağlanma dayanımına etkisini değerlendirmiş-lerdir.…”
Section: Discussionunclassified